Implementasi Keterampilan Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja Guru di Madrasah Tsanawiyah Al-Rasyid Sungai Rawa Kecamatan Batang Tuaka Kabupaten Indragiri Hilir - Haidir Haidir; Badrussyamsi Badrussyamsi; Dewi Hasanah (Departement of Mathematics Education, 2023)
This study discusses the implementation, factors and leadership efforts of the madrasa head in improving teacher performance at Madrasah Tsanawiyah Al-Rasyid Sungai Rawa, Batang Tuaka District, Indragiri Hilir Regency. This research is a qualitative method with a descriptive analysis approach. The main resource persons in this study were the Head of Madrasah and Teachers. The results of the study determined the first finding that the implementation of the leadership skills of the Head of Madrasah Tsanawiyah Al-Rasyid Sungai Rawa in general was quite good, but there were still several categories that had not been fulfilled optimally including increasing mastery of the educational foundation, using media and learning resources, and evaluating learning outcomes, for factors that impede the improvement of teacher performance including mastery of teaching materials, class management that has not been maximized, lack of use of learning methods, inadequate use of media or learning resources and supervision or assessment activities that have not been carried out optimally so that it hinders teachers in improving their performance as educators. and efforts made by the head of the madrasa include providing counseling to teachers in the madrasa providing training and motivation in the use of learning media.